Food Safety Risk Communication between the Food Regulator and Consumer in China: An Evolutionary Game Perspective. (18th August 2021) - Zhu, Ying; Chu, May; Wen, Xiaowei; Wang, Yiqin
Abstract : Food safety risk communication has attracted widespread attention in China. The government is the leader in food risk communication. It has even more impact on consumers' willingness to communicate food risk. Thus, this paper constructs a risk communication game model composed of the central government, local government, and consumers under food safety regulatory agencies in China. Based on the evolutionary game theory, we achieved the evolutionary stable equilibrium points under complying different constraint conditions by solving the replicator dynamic equations of parties in the dynamic system. In the end, some numerical examples have been displayed to simulate the agents' choices. The results show that penalty cost, governance intensity, communication cost, and reputation of the government have an essential impact on consumers' enthusiasm for food safety risk communication decision-making behavior. Furthermore, the choice of food safety risk communication strategies is performed with a dynamic process, which is constantly adjusted and optimized. The evolutionary game system can converge on an ideal state under certain conditions. Moreover, this study proposes suggestions and measures conducive to the tripartite game, which can offer valuable guidance on food risk communication practice and improve government efficiency in China. This research can provide the evolutionary mechanism and broaden our understanding of the relationship between food safety risk governance and food risk communication strategies.